ISOLATION OF ETHYL TRANS-P-METHOXYCINNAMATE FROM Kaempferia galanga L. RHIZOMES BY USING N-HEXANE - Ingeswari, Aulya Vidiana; Khozin, Muhamad Nur; Fadlan, Arif; Santoso, Mardi; Nugraheni, Zjahra Vianita; Sarmoko (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2024)
Kaempferia galanga L. rhizomes contain ethyl trans-p-methoxycinnamate as a major secondary metabolite compound and biomarker. Various extraction methods with different solvents can isolate ethyl trans-p-methoxycinnamate with potential bioactivities. This paper reported the isolation of ethyl trans-p-methoxycinnamate from two varieties of K. galanga L. rhizomes by maceration in n-hexane. The small and large varieties of K. galanga samples produced ethyl trans-p-methoxycinnamate in 1.43% and 1.84% yields, higher than other methods and polar solvents of previous research. Structural elucidation of the obtained ethyl trans-p-methoxycinnamate was performed by FTIR, MS, and 1H NMR spectroscopies.